THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN LEARNING SERVICES RANKING DELI SERDANG - Ben Setiawan (CV. Radja Publika, 2022)
This study aims to determine and analyze the effect of service quality which consists of physical evidence, reliability, responsiveness, assurance, and empathy on customer satisfaction for users of the Deli Serdang Ranking Tutoring services. The population in this study were high school students who used Ranking tutoring services as many as 218 people. The sample in this research is 70 respondents. Primary data collection was carried out using a questionnaire measured by a Likert scale. Secondary data obtained from books related to research. The analysis technique used is multiple linear regression analysis. The results of the data research show that service quality includes physical evidence, reliability, responsiveness, assurance, and empathy simultaneously has a positive and significant effect on customer satisfaction in users of the Deli Serdang Ranking Tutoring services. The results of the partial significance test stated that physical evidence, responsiveness, assurance, and empathy had a positive and significant effect on customer satisfaction, while reliability had a positive and insignificant effect on customer satisfaction for users of the Deli Serdang Ranking Tutoring services. And the result of the F test is Ftable = 2.36, where Fcount > Ftable (63.263 > 2.36) which means simultaneously there is a positive and significant influence from the independent variables namely physical evidence, reliability, responsiveness, assurance, and empathy on the dependent variable on student satisfaction in the Deli Serdang Ranking Tutoring.